Innovative Work Behavior and the Impact of Organizational Culture - Hajad Priyadi; Surono Surono; Chairul Hakim (Universitas 45 Surabaya, 2023)
This article aims to examine the influence of entrepreneurial leadership and organizational culture on performance through innovative work behavior. The research sample is 301 people, who are non-managerial employees in the city of Bandung. Data was shared via Google form and processed using structural equation modeling (SEM) with the LISREL program. The results of data processing state that entrepreneurial leadership has a significant and negative effect on innovative work behavior, organizational culture has a significant and positive effect on innovative work behavior, innovative work behavior has a significant and positive effect on performance, entrepreneurial leadership is not significant on performance, organizational culture is not significant on performance